Electrocardiographic and Electrophysiologic Characteristics of Ventricular Extrasystoles Arising from the Aortomitral Continuity - Konstantinos P. Letsas; Michael Efremidis; George Kollias; Sotirios Xydonas; Antonios Sideris (Cardiology Research and Practice)
Left ventricular outflow tract arrhythmias originating from the aortomitral continuity, the left coronary cusp, the superior basal septum, and the epicardial left ventricular summit display common electrocardiographic and electrophysiological features, probably due to the close proximity of those locations. Catheter ablation of these arrhythmias can be challenging. The case of a 68-year-old male with frequent premature ventricular extrasystoles arising from the aortomitral continuity of the basal left ventricle is described. The electrocardiographic and electrophysiologic characteristics of this arrhythmia are discussed.